Investigating the psammophilic karyorelictean ciliate families Kentrophoridae and Cryptopharyngidae (Protista, Ciliophora): molecular phylogeny, geographic distributions and a brief revision including descriptions of a new genus, a new species and a new combination - Mingzhen Ma; Danxu Tang; Wen Song; Lifang Li; Igor V. Dovgal; Khaled A. S. Al-Rasheid; Hunter N. Hines; Ying Yan (Marine Life Science & Technology, 2024)
Psammophillic ciliates are an integral part of the foodweb despite being underrepresented in terms of molecular phylogeny and modern taxonomy. To investigate the karyorelictean group, sampling was conducted in interstitial marine habitats in China for ciliates living between the sand grains, resulting in an examination of the families Cryptopharyngidae Jankowski, 1980 and Kentrophoridae Jankowski, 1980. Three species, i.e., Cryptopharynx setigerus Kahl, 1928, Kentrophoros fasciolatus (Sauerbrey, 1928) Foissner, 1995 and K. fistulosus (Fauré-Fremiet, 1950) Foissner, 1995, are clearly recognized as being cosmopolitan, while other species await further recording. Phylogenetic analyses were carried out based on updated data. These revealed that the families Cryptopharyngidae and Kentrophoridae are closely related, and most genera studied are monophyletic, although Cryptopharynx qingdaoensis n. sp. is located within the Kentrophoridae branch. Brief revisions of two genera, namely Cryptopharynx Kahl, 1928 and Kentrophoros Sauerbrey, 1928, are provided including keys to the identification of nine species belonging to the former and 12 species belonging to the latter. One new genus, Parakentrophoros n. gen., and one new species, Cryptopharynx qingdaoensis n. sp., are described and a new combination, Parakentrophoros canalis (Wright, 1982) n. comb., is established. Finally, it appears that the subapical oral apparatus undergoes a gradual degeneration process from Cryptopharyngidae to Kentrophoridae.

Linking multi-gene and morphological data in the subclass Scuticociliatia (Protista, Ciliophora) with establishment of the new family Homalogastridae fam. nov. - Mingjian Liu; Limin Jiang; Zhe Zhang; Fan Wei; Honggang Ma; Zigui Chen; Khaled A. S. Al-Rasheid; Hunter N. Hines; Chundi Wang (Marine Life Science & Technology, 2024)
Scuticociliatia is one of the most species-rich subclasses in the phylum Ciliophora. The evolutionary relationships among Scuticociliatia groups have long been very unclear due to the homogeneity of morphology and insufficiency of molecular data. With morphological and multi-gene-based molecular data presented here, the evolutionary phylogeny of several Scuticociliatia taxa that were hitherto especially poorly defined is analyzed and discussed. The results indicate: (1) all scuticociliates cluster into two well supported and one poorly supported group, representing three order-level taxa; (2) with the support of both morphological and molecular data, a new family Homalogastridae fam. nov. is proposed in the order Philasterida; (3) Parauronema is formally transferred to Uronematidae and Potomacus is treated as incertae sedis in the order Philasterida, therefore Parauronematidae is proposed to be a junior synonym of Uronematidae; (4) the genus Madsenia and the species Parauronema longum and Pseudocyclidium longum are treated as incertae sedis , while the genus Protophyra should be maintained in the family Ancistridae. In addition, the putative secondary structure of internal transcribed spacer 2 (ITS2) of representative taxa from the three orders of Scuticociliatia are analyzed, and consensus structures and nucleotide composition in each order are exhibited.

Novel findings on the mitochondria in ciliates, with description of mitochondrial genomes of six representatives - Tengteng Zhang; Jinyu Fu; Chao Li; Ruitao Gong; Khaled A. S. Al-Rasheid; Naomi A. Stover; Chen Shao; Ting Cheng (Marine Life Science & Technology, 2024)
Determining and comparing mitochondrial genomes (mitogenomes) are essential for assessing the diversity and evolution of mitochondria. Ciliates are ancient and diverse unicellular eukaryotes, and thus are ideal models for elucidating the early evolution of mitochondria. Here, we report on six new mitogenomes of spirotrichs, a dominant ciliate group, and perform comparative analyses on 12 representative species. We show that: (1) the mitogenomes of spirotrichs are linear structures with high A+T contents (61.12–81.16%), bidirectional transcription, and extensive synteny (except for the nad5 , ccmf and cob genes in Euplotia); (2) the non-split of NADH dehydrogenase subunit 2 gene ( nad2 ) is a plesiomorphy of ciliates, whereas it has evolved into a split gene in Spirotrichea (apart from Euplotes taxa), Oligohymenophorea, and Armophorea; (3) the number of small subunit ribosomal proteins (rps) encoded in mitogenomes increases in the later branching classes of ciliates, whereas rps8 shows a loss trend during the evolution of Euplotes taxa; (4) the mitogenomes of spirotrichs exhibit A/T codon bias at the third position, and the codon bias is mainly due to DNA mutation in oligotrichs, hypotrichs and Diophrys appendiculata ; (5) the phylogenetic position of D. appendiculata is unstable and controversial based on both phylogenetic analyses and mitogenome evidence. In summary, we investigated the mitogenome diversity of spirotrichs and broadened our understanding of the evolution of mitochondria in ciliates.

Multi-gene-based investigation on the molecular phylogeny of the hypotrichous family Strongylidiidae (Protista, Ciliophora), with notes on the ontogeny of a new genus and new species - Wenya Song; Shijing Zhang; Yuqing Li; Honggang Ma; Qiyu Li; Xiaotian Luo; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiaoteng Lu (Marine Life Science & Technology, 2024)
Ciliates in the subclass Hypotrichia have long been difficult to classify as they are one of the most polymorphic and highly differentiated groups, leading to their systematics remaining unresolved. Phylogenetic relationships within the hypotrich family Strongylidiidae have been ambiguous due to discordance between the morphological and genetic data. In this study, a new strongylidiid genus Heterouroleptus is established, mainly based on the novel mode of origin of the ventral cirral rows: left ventral cirral row (LVR) originates from frontal–ventral–transverse cirral anlagen (FVTA) III (anterior portion), IV (middle portion), and V (rear portion); right ventral cirral row comes from the entire FVTA VI. A new species, Heterouroleptus weishanensis gen. nov., sp. nov., is investigated along with the morphometric and molecular data from a population of Strongylidium wuhanense . Eight new sequences and nuclear gene markers (single-gene and multi-gene) are provided to analyze the phylogenetic relationships of strongylidiids, with the COI gene utilized to uncover further genetic information at species level and below. The results reveal that: (1) Strongylidiidae is monophyletic and has a close relationship with Dorsomarginalia; (2) Heterouroleptus gen. nov. forms a clade that is sister to all the other strongylidiids; (3) Hemiamphisiella Foissner, 1988 and Pseudouroleptus Hemberger, 1985 should not be synonyms, and both genera should be subdivided due to their variable morphological characteristics; (4) LVR originating from three anlagen is a plesiomorphy of Strongylidiidae. The discovery of the origin of the LVR not only contributes to the establishment of the genus Heterouroleptus , but also helps to improve the diagnosis of the family Strongylidiidae.

Exploring the biogeography, morphology, and phylogeny of the condylostomatid ciliates (Alveolata, Ciliophora, Heterotrichea), with establishment of four new Condylostoma species and a revision including redescriptions of five species found in China - Yong Chi; Fan Wei; Danxu Tang; Changjun Mu; Honggang Ma; Zhe Wang; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiangrui Chen (Marine Life Science & Technology, 2024)
Species of the ciliate class Heterotrichea Stein, 1859 are a cosmopolitan group of unicellular eukaryotic microorganisms, many of which have been widely used as models in various fields of research such as regenerative biology, functional ecology, environmental toxicology, and symbiotic behavior. However, species identification in the heterotrich family Condylostomatidae, especially the most species-rich and type genus Condylostoma Bory de Saint-Vincent, 1824, remains challenging due to incomplete original descriptions, few reliable distinguishing characters, and overlapping features between different species. This study presents an updated revision of Condylostoma and its related genus Condylostomides da Silva Neto, 1994 based on descriptions of five species, including nine populations collected from China, using both morphological and molecular methods. The main findings are as follows: (1) 43 nominal species and about 130 populations are reviewed, resulting in the recognition of 30 valid species of Condylostoma and eight valid species of Condylostomides ; (2) keys, synonyms, biogeographic distributions and amended/improved diagnoses of all valid species are provided; (3) based on the available data, four new Condylostoma species ( C. marinum sp. nov., C. petzi sp. nov., C. villeneuvei sp. nov., and C. microstomum sp. nov.), one new combination ( Condylostomides minimus (Dragesco, 1954) comb. nov. & nom. corr.), and two corrected names ( Condylostoma ancestrale Villeneuve-Brachon, 1940 nom. corr. and Condylostomides nigrus (Dragesco, 1960) nom. corr.) are suggested; (4) cryptic species are detected and proposed for the first time to form the Condylostoma curvum species complex; (5) three highly confusing Condylostoma species, C. kris , C. spatiosum , and C. minutum , are redefined for the first time based on modern taxonomic methods; (6) a ‘flagship’ species, Condylostomides coeruleus , is recorded for the first time from the continent of Asia, substantially expanding its biogeography; (7) ciliature adjacent to the distal end of the paroral membrane within the family Condylostomatidae is uniformly defined as frontal membranelles and is classified into three patterns according to the arrangement of kinetosomes, which serve as important key features.

On four epibiotic peritrichous ciliates (Protozoa, Ciliophora) found in Lake Weishan Wetland: morphological and molecular data support the establishment of a new genus, Parapiosoma gen. nov., and two new species - Tong Wu; Ting Cheng; Xiao Cao; Yaohan Jiang; Khaled A. S. Al-Rasheid; Alan Warren; Zhe Wang; Borong Lu (Marine Life Science & Technology, 2023)
During a study on the diversity of ciliated protists in Lake Weishan Wetland, the largest wetland in northern China, four epibiotic sessilid peritrichs were isolated from aquatic host animals. Two of them, i.e., Epistylis cambari Kellicott, 1885 and Epistylis lwoffi Fauré-Fremiet, 1943, were known species whereas the other two, i.e., Parapiosoma typicum gen. nov., sp. nov. and Orborhabdostyla gracilis sp. nov., are new to science. The new genus Parapiosoma gen. nov. is characterized by its branched non-contractile stalk, everted peristomial lip, obconical macronucleus and transverse silverlines. Two species are assigned to the new genus, namely Parapiosoma typicum sp. nov. and Parapiosoma gasterostei (Fauré-Fremiet, 1905) comb. nov. Morphologically, P. typicum sp. nov. is recognized by its goblet-shaped zooids, single-layered peristomial lip, dichotomously branched stalk, and infundibular polykinety 3 (P3) containing three equal-length rows. Orborhabdostyla gracilis sp. nov. is characterized by its slender zooid, curved macronucleus, and three equal-length rows in infundibular P3. Improved diagnoses and redescriptions of E. cambari and E. lwoffi are provided including, for the first time, data on the ciliature of E. cambari . Phylogenetic analyses based on SSU rDNA, ITS1-5.8S rDNA -ITS2, and LSU rDNA sequence data strongly support the assertion that the family Epistylididae comprises morphospecies with different evolutionary lineages and indicate that Parapiosoma gen. nov. may represent a new taxon at family level.

Biodiversity of freshwater ciliates (Protista, Ciliophora) in the Lake Weishan Wetland, China: the state of the art - Zhe Wang; Yong Chi; Tao Li; Wenya Song; Yunfeng Wang; Tong Wu; Gongaote Zhang; Yujie Liu; Honggang Ma; Weibo Song; Khaled A. S. Al-Rasheid; Alan Warren; et al. (Marine Life Science & Technology, 2022)

New considerations on the phylogeny of Sessilida (Protista: Ciliophora: Peritrichia) based on multiple-gene information, with emphasis on colonial taxa - Zhe Wang; Xiaoting Feng; Lifang Li; Khaled A. S. Al-Rasheid; Alan Warren; Chundi Wang; Zemao Gu (Marine Life Science & Technology, 2022)

Corrigendum: Morphology and Molecular Phylogeny of Four Trachelocercid Ciliates (Protozoa, Ciliophora, Karyorelictea) Found in Marine Coastal Habitats of Northern China, With Description of a New Genus, Two New Species and a New Combination - Mingzhen Ma; Yuqing Li; Honggang Ma; Khaled A. S. Al-Rasheid; Alan Warren; Yurui Wang; Ying Yan (Frontiers in Marine Science, 2021)

Morphology and Molecular Phylogeny of Four Trachelocercid Ciliates (Protozoa, Ciliophora, Karyorelictea) Found in Marine Coastal Habitats of Northern China, With Description of a New Genus, Two New Species and a New Combination - Mingzhen Ma; Yuqing Li; Honggang Ma; Khaled A. S. Al-Rasheid; Alan Warren; Yurui Wang; Ying Yan (Frontiers in Marine Science, 2021)
The morphology of four trachelocercid ciliates, Paratrachelocerca typica gen. nov., spec. nov., Trachelolophos monocaryon ( Dragesco, 1965 ) comb. nov. (original combination: Tracheloraphis monocaryon Dragesco, 1965 ), Tracheloraphis katzae spec. nov., and Tracheloraphis colubis ( Kahl, 1933 ) Xu et al., 2011 were studied in live and protargol-stained specimens. All samples were isolated from the intertidal zone of sandy beaches at Qingdao, China. The new genus Paratrachelocerca can be distinguished from other trachelocercid genera mainly by the three circumoral kineties each composed of a row of dikinetids and the absence of a brosse or ciliary tuft in the oral cavity. The detailed investigation on the poorly described Tracheloraphis monocaryon ( Dragesco, 1965 ) reveals that its oral infraciliature includes one uninterrupted circumoral kinety and a conspicuous ciliary tuft in the center of the oral cavity, which is consistent with the genus Trachelolophos rather than Tracheloraphis . Therefore, this species is transferred to Trachelolophos as Trachelolophos monocaryon ( Dragesco, 1965 ) comb. nov. Tracheloraphis katzae spec. nov. can be recognized by the combination of its minute brownish cortical granules and 9–15 somatic kineties. The small subunit (SSU) rDNA of each species was sequenced for the first time. Phylogenetic analyses of the SSU rDNA show that Paratrachelocerca typica gen. nov., spec. nov. clusters with Apotrachelocerca arenicola ( Kahl, 1933 ) Xu et al., 2011 in a group that is sister to all other trachelocercids.

Morphogenesis of the Ciliature During Sexual Process of Conjugation in the Ciliated Protist Euplotes raikovi - Usman Asghar; Yong Chi; Yunyi Gao; Borong Lu; Yaohan Jiang; Ruitao Gong; Honggang Ma; Khaled A. S. Al-Rasheid; Feng Gao (Frontiers in Marine Science, 2021)
Morphogenesis is an important process that widely occurs in almost all the organisms, including the ciliated protists. Ciliates are a large group of single-celled eukaryotes that can reproduce asexually (e.g., binary fission) and perform sexual process (e.g., conjugation). Morphogenesis happens in both asexual reproduction and sexual process in ciliates and the reorganization during conjugation is more complex. However, studies of morphogenesis focusing on conjugation are very limited. Here we studied the morphogenetic process during conjugation in the marine species Euplotes raikovi Agamaliev, 1966. The results indicate that: (1) the ciliature in the ventral side reorganizes twice during sexual process, i.e., conjugational and postconjugational reorganization; (2) the adoral zone of membranelles (AZM) is generated de novo in a pouch beneath the cortex during both reorganizations, with the anterior part generated during the first reorganization, while the posterior part formed during the second reorganization; (3) the frontoventral-transverse (FVT) cirri anlagen are formed de novo in both processes with the fragmentation pattern of 2:2:3:3:2; (4) one left marginal cirrus is generated de novo during both reorganizations; and (5) the dorsal ciliature remains intact during the whole process, except that the two caudal cirri originate from the end of the right-most two dorsal kineties during both reorganizations. Comparisons of the morphogenetic process during conjugation demonstrate a considerably stable pattern within Euplotes while the patterns vary dramatically among different ciliate groups.

Morphology and molecular phylogeny of two new species of Spirostrombidium (Ciliophora, Oligotrichia), with a key to the species of Spirostrombidium - Rui Wang; Wen Song; Zhenzhen Yi; Khaled A. S. Al-Rasheid; Xiaozhong Hu (Systematics and Biodiversity, 2018)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

New contributions to the biodiversity of ciliates (Protozoa, Ciliophora) from Antarctica, including a description of Gastronauta multistriata nov. spec. - Yuan Xu; Chen Shao; Xinpeng Fan; Alan Warren; Khaled A. S. Al-Rasheid; Weibo Song; Norbert Wilbert (Polar Biology, 2016)

Biodiversity of oligotrich ciliates in the South China Sea: description of three new Strombidium species (Protozoa, Ciliophora, Oligotrichia) with phylogenetic analyses - Wen Song; Xiaolu Zhao; Weiwei Liu; Xiaozhong Hu; Saleh A. Al-Farraj; Khaled A. S. Al-Rasheid; Weibo Song; Alan Warren (Systematics and Biodiversity, 2015)

Redefinition of the hypotrichous ciliate Uncinata , with descriptions of the morphology and phylogeny of three urostylids (Protista, Ciliophora) - Xiaotian Luo; Feng Gao; Khaled A. S. Al-Rasheid; Alan Warren; Xiaozhong Hu; Weibo Song (Systematics and Biodiversity, 2015)

Molecular phylogenetic lineage of Plagiopogon and Askenasia (Protozoa, Ciliophora) revealed by their gene sequences - An Liu; Zhenzhen Yi; Xiaofeng Lin; Xiaozhong Hu; Saleh A. Al-Farraj; Khaled A. S. Al-Rasheid (Journal of Ocean University of China, 2015)

Recognizing the importance of exposure–dose–response dynamics for ecotoxicity assessment: nitrofurazone-induced antioxidase activity and mRNA expression in model protozoan Euplotes vannus - Yazhen Hong; Shuxing Liu; Xiaofeng Lin; Jiqiu Li; Zhenzhen Yi; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2015)

Taxonomy and molecular phylogeny of four Strombidium species, including description of S. pseudostylifer sp. nov. (Ciliophora, Oligotrichia) - Wen Song; Jiamei Li; Weiwei Liu; Khaled A. S. Al-rasheid; Xiaozhong Hu; Xiaofeng Lin (Systematics and Biodiversity, 2015)

A phylogenetic reconsideration of suctorian ciliates ( P rotista, C iliophora, P hyllopharyngea) based on small subunit r RNA gene sequences - Xiaolu Zhao; Miao Miao; Xiangrui Chen; Honggang Ma; Khaled A. S. Al‐Rasheid (Zoologica Scripta, 2014)
Compared with other ciliated protozoa, molecular studies of phylogenetic relationships within the subclass Suctoria are rare. In this work, phylogenetic analyses focusing on this group were performed based on all data available. In addition, the small subunit ribosomal RNA ( SSU r RNA ) genes of three suctorian ciliates ( Acineta compressa , Acineta tuberosa and Paracineta limbata ) were newly sequenced. Furthermore, the putative secondary structures of the variable region 2 of the SSU r RNA gene were predicted and compared within the Suctoria. Our results show that (i) there is support for the monophyly of the subclass Suctoria, which is a sister clade to the cyrtophorids; (ii) based on combined morphologic and molecular features, we propose the following evolutionary routine within the Suctoria: Exogenina – Evaginogenina – Endogenina; (iii) the similarities of the secondary structures of the V2 region and the SSU r RNA gene sequences within the subclass Suctoria are consistent with the branching of the phylogenetic lineages.

Influence of enumeration time periods on analyzing colonization features and taxonomic relatedness of periphytic ciliate communities using an artificial substratum for marine bioassessment - Wei Zhang; Henglong Xu; Yong Jiang; Mingzhuang Zhu; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2012)

Can body-size patterns of ciliated zooplankton be used for assessing marine water quality? A case study on bioassessment in Jiaozhou Bay, northern Yellow Sea - Yong Jiang; Henglong Xu; Wei Zhang; Mingzhuang Zhu; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2012)

Colonization dynamics in trophic-functional structure of periphytic protist communities in coastal waters - Wei Zhang; Henglong Xu; Yong Jiang; Mingzhuang Zhu; Khaled A. S. Al-Rasheid (Marine Biology, 2012)

Influence of sampling sufficiency on biodiversity analysis of microperiphyton communities for marine bioassessment - Henglong Xu; Wei Zhang; Yong Jiang; Mingzhuang Zhu; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2012)

Taxonomy, morphology and molecular systematics of a new oligotrich ciliate, Williophrya maedai gen. nov., sp. nov., with redescriptions of Strombidium basimorphum and Pseudotontonia simplicidens (Protozoa, Ciliophora, Oligotrichia) - WEIWEI LIU; ZHENZHEN YI; ALAN WARREN; KHALED A. S. AL-RASHEID; SALEH A. AL-FARRAJ; XIAOFENG LIN; WEIBO SONG (Systematics and Biodiversity, 2011)

An approach to determining potential surrogates for analyzing ecological patterns of planktonic ciliate communities in marine ecosystems - Henglong Xu; Yong Jiang; Wei Zhang; Mingzhuang Zhu; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2011)

Application of an indicator based on taxonomic relatedness of ciliated protozoan assemblages for marine environmental assessment - Henglong Xu; Yong Jiang; Khaled A. S. Al-Rasheid; Saleh A. Al-Farraj; Weibo Song (Environmental Science and Pollution Research, 2011)

Spatial variation in taxonomic distinctness of ciliated protozoan communities at genus-level resolution and relationships to marine water quality in Jiaozhou Bay, northern China - Henglong Xu; Yong Jiang; Khaled A. S. Al-Rasheid; Weibo Song; Alan Warren (Hydrobiologia, 2011)

Molecular evolution of Cinetochilum and Sathrophilus (Protozoa, Ciliophora, Oligohymenophorea), two genera of ciliates with morphological affinities to scuticociliates - Qianqian Zhang; Miao Miao; Michaela C. Strüder‐Kypke; Khaled A. S. Al‐Rasheid; Saleh A. Al‐Farraj; Weibo Song (Zoologica Scripta, 2011)
Zhang, Q., Miao, M., Strüder‐Kypke, M. C., Al‐Rasheid, K. A. S., Al‐Farraj, S. A. & Song, W. (2011). Molecular evolution of Cinetochilum and Sathrophilus (Protozoa, Ciliophora, Oligohymenophorea), two genera of ciliates with morphological affinities to scuticociliates. — Zoologica Scripta , 40 , 317–325. The ciliate order Loxocephalida sensu Li et al. (2006) has been considered to be systematically uncertain within the subclass Scuticociliatia. Loxocephalids display mixed morphological features and morphogenetic patterns that are found in two different oligohymenophorean subclasses: scuticociliates and hymenostomes. To reveal their phylogenetic positions, molecular information on this group is urgently needed but still inadequate. In the present study, we have sequenced the small subunit rRNA gene of two newly described loxocephalids, Cinetochilum ovale Gong & Song 2008; and Sathrophilus planus Fan et al. 2010; which have never been discussed based on molecular analysis. Results show: (i) all phylogenetic trees are nearly identical in placing Cinetochilum closest to the subclass Apostomatia and form a monophyletic group divergent from the typical scuticociliates, (ii) the genus Sathrophilus , together with Anoplophrya , a poorly known Astomatia, forms a peripheral branch separated from the scuticociliatian assemblage and (iii) the affiliation of the loxocephalid genera sensu Li et al. (2006) is not confirmed due to a dispersion in four deeply diverged clades. In addition, the polyphyly of the genus Cyclidium, shown in previous studies, is confirmed by our phylogenetic analyses and supported by the approximately unbiased test based on the new database in this work.

On four closely related hypotrichous ciliates (Protozoa, Ciliophora, Spirotrichea): molecular characters, interspecific relationships and phylogeny defined with multigene sequence information - Feng Gao; Zhenzhen Yi; Zigui Chen; A. S. Al-Rasheid Khaled; Weibo Song (Acta Oceanologica Sinica, 2010)

Planktonic protist communities in semi-enclosed mariculture waters: temporal dynamics of functional groups and their responses to environmental conditions - Henglong Xu; Alan Warren; Khaled A. S. Al-Rasheid; Mingzhuang Zhu; Weibo Song (Acta Oceanologica Sinica, 2010)

Temporal species distributions of planktonic protist communities in semi-enclosed mariculture waters and responses to environmental stress - Henglong Xu; Mingzhuang Zhu; Yong Jiang; A. S. Al-Rasheid Khaled (Acta Oceanologica Sinica, 2010)

Molecular phylogeny of three ambiguous ciliate genera: Kentrophoros , Trachelolophos and Trachelotractus (Alveolata, Ciliophora) - Shan Gao; Michaela C. Strüder-Kypke; Khaled A. S. Al-Rasheid; Xiaofeng Lin; Weibo Song (Zoologica Scripta, 2010)

Molecular phylogeny of Nothoholosticha (Protozoa, Ciliophora, Urostylida) and systematic relationships of the Holosticha -complex - Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2010)

Protocruzia, a highly ambiguous ciliate (Protozoa; Ciliophora): Very likely an ancestral form for Heterotrichea, Colpodea or Spirotrichea? With reevaluation of its evolutionary position based on multigene analyses - LiFang Li; Stoeck Thorsten; Shin Mann Kyoon; A. S. Al-Rasheid Khaled; A. Al-Khedhairy Bdulaziz; WeiBo Song (Science China Life Sciences, 2010)

Phylogeny of six oligohymenophoreans (Protozoa, Ciliophora) inferred from small subunit rRNA gene sequences - Zhenzhen Yi; Weibo Song; Jun Gong; Alan Warren; Khaled A. S. Al‐Rasheid; Saud Al‐Arifi; Abdulaziz A. Al‐Khedhairy (Zoologica Scripta, 2009)
The small subunit rRNA (SSrRNA) genes of six marine oligohymenophoreans, namely Uronemella filificum , Schizocalyptra sp.‐WYG07060701, Schizocalyptra aeschtae , Pleuronema sinica , P. czapikae and Paratetrahymena sp., were sequenced. Phylogenetic trees were constructed with four different methods to assess the inter‐ and intrageneric relationships among the scuticociliates and the phylogenetic assignment of the order Loxocephalida. The SSrRNA phylogeny indicates that: (i) Paratetrahymena is most closely related to Cardiostomatella ; (ii) the order Loxocephalida and the family Uronematidae both appear to be polyphyletic; (iii) the order Philasterida is a well‐defined taxon; (iv) Cyclidium porcatum falls outside the order Pleuronematida in all analyses; (v) the validity of the genus Uronemella is confirmed; (vi) Schizocalyptra is a member of the family Pleuronematidae. Furthermore, the predicted secondary structures of the variable region 4 of the SSrRNA gene sequences show that the size of the terminal bulge in Helix E23–7 is probably different for the orders Philasterida and Pleuronematida. Also, compared to Uronema and Homalogastra , Uronemella has distinct patterns in Helices E23–1, E23–7, E23–8 and E23–9.